The extend and nature of curriculum change in the historically black technical colleges in the Limpopo Province - Bopape, Matome Zacharia (My University, 2003)
Refer to the document
Thesis (M. Dev.) -- University of Limpopo, 2003
Keywords: Curriculum change; Technical colleges; Transformation; Education; Curriculum change -- South Africa -- Limpopo; Education -- Research; Education -- Curricula -- South Africa -- Limpopo